Designing cellulosic and nanocellulosic sensors for interface with a protease sequestrant wound-dressing prototype: Implications of material selection for dressing and protease sensor design. (November 2017) - Fontenot, Krystal R; Edwards, J Vincent; Haldane, David; Pircher, Nicole; Liebner, Falk; Condon, Brian D; Qureshi, Huzaifah; Yager, Dorne
Interfacing nanocellulosic-based biosensors with chronic wound dressings for protease point of care diagnostics combines functional material properties of high specific surface area, appropriate surface charge, and hydrophilicity with biocompatibility to the wound environment. Combining a protease sensor with a dressing is consistent with the concept of an intelligent dressing, which has been a goal of wound-dressing design for more than a quarter century. We present here biosensors with a nanocellulosic transducer surface (nanocrystals, nanocellulose composites, and nanocellulosic aerogels) immobilized with a fluorescent elastase tripeptide or tetrapeptide biomolecule, which has selectivity and affinity for human neutrophil elastase present in chronic wound fluid. The specific surface area of the materials correlates with a greater loading of the elastase peptide substrate. Nitrogen adsorption and mercury intrusion studies revealed gas permeable systems with different porosities (28–98%) and pore sizes (2–50 nm, 210 µm) respectively, which influence water vapor transmission rates. A correlation between zeta potential values and the degree of protease sequestration imply that the greater the negative surface charge of the nanomaterials, the greater the sequestration of positively charged neutrophil proteases. The biosensors gave detection sensitivities of 0.015–0.13 units/ml, which are at detectable human neutrophil elastase levels present in chronic wound fluid. Thus, the physical and interactive biochemical properties of the nano-based biosensors are suitable for interfacing with protease sequestrant prototype wound dressings. A discussion of the relevance of protease sensors and cellulose nanomaterials to current chronic wound dressing design and technology is included.